High-Salt Diet Accelerated the Decline of Residual Renal Function in Patients With Peritoneal Dialysis - Gong, Nirong; Zhou, Chun; Hu, Jianxia; Zhong, Xiaohong; Yi, Zhixiu; Zhang, Tingting; Yang, Cong; Lin, Yanhong; Tian, Jianwei; Qin, Xianhui; Hu, Liping; Jiang, Jianping (Frontiers in Medicine, 2021)
Objective: This study aims to investigate the relationship between dietary salt intake and residual renal function in peritoneal dialysis (PD) patients. Methods: The daily salt intake of the patients was calculated based on a 3 day dietary record. Sixty-two patients were divided into three groups: 33 patients in the low salt intake group (salt intake <6.0 g/day), 17 in the medium salt intake group (salt intake 6.0 to <8.0 g/day), and 12 in the high salt intake group (salt intake ≥8.0 g/day). Regular follow-up was conducted every 3 months. Urine volume, peritoneal ultrafiltration volume, and other clinical indicators were recorded. Biochemical indexes were detected to evaluate the changes in residual renal function and peritoneal function during follow-up. Results: A positive correlation between dietary sodium intake and sodium excretion was found. During 12-month follow-up, a decrease of residual renal function showed a significant difference among the three groups (p = 0.041) (15.3 ± 27.5 vs. 12.5 ± 11.5 vs. 32.9 ± 18.4 L/W/1.73 m2 in the low-, medium-, and high salt intake groups, respectively). Consistently, a higher decline of residual renal function (adjusted β, 20.37; 95% CI, 2.83, 37.91) was found in participants with high salt intake (salt intake ≥8 g/day) compared with those in non-high salt intake. Conclusion: Our study showed that the sodium excretion by peritoneal dialysis was positively correlated with dietary sodium intake in PD patients. The high salt intake diet (salt intake ≥8 g/day) may lead to a faster decline of residual renal function in PD patients.